Translating English Military Terminology on Special Operations Forces into Ukrainian - Kalynovska, Iryna (My University, 2024)
Military translation in Ukraine is constantly developing thanks to the intensification of measures of international defence cooperation, an adaptation of the Armed Forces of Ukraine to NATO standards, the need to translate important military and political documents, as well as oral and written translation of military-technical and military-special translation [2]. In the context of the Russian war in Ukraine, military terminology acts as a key tool in mutual understanding between different types of military forces, government organizations, and international partners [3], which determines the relevance of our research, the object of which is special operations forces terminology.
Keywords: translation; military terminology; term; special operations forces